The Ideal HPC Programming Language. - LOH, EUGENE (Communications of the ACM, 2010)
The article discusses the results of computer programming language studies conducted by Sun Microsystems in the context of a High Productivity Computing Systems (HPCS) program run by the U.S. Defense Advanced Research Projects Agency (DARPA). The studies attempted to determine what the optimal characteristics of a high-performance computing (HPC) programming language would be. The traditional language, Fortran, was actually found to be surprisingly effective. The main obstacles to well-written programs often involved artifacts introduced by the specific hardware limitations of central processing units, or questionable choices in a program's conceptual design, rather than limitations in the language itself.